A Study of Down-Conversion in Lanthanide Ions Doped Glasses for the Applications in Solar Cells: Exploring Lanthanide Ion Doping in Glasses for Efficient Energy Conversion (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Solar energy is a renewable source of energy with low negative impact on the environment. For the enhancement of conversion of energy various techniques and material are studied by researchers. Upconversion and down conversion are two most important methods for conversion of energy from low to high and high to low frequency. Lanthanide ions are highly promising candidates for getting up and down conversion.